Extended Cooperation in Clinical Studies through Exchange of CDISC Metadata between Different Study Software Solutions - Kuchinke, W.; Wiegelmann, S.; Verplancke, P.; Ohmann, C. (Methods of Information in Medicine, 2006)
Objectives: Our objectives were to analyze the possibility of an exchange of an entire clinical study between two different and independent study software solutions. The question addressed was whether a software-independent transfer of study metadata can be performed without programming efforts and with software routinely used for clinical research.Methods: Study metadata was transferred with ODM standard (CDISC). Study software systems employed were MACRO (InferMed) and XTrial (XClinical). For the Proof of Concept, a test study was created with MACRO and exported as ODM. For modification and validation of the ODM export file XML-Spy (Altova) and ODM-Checker (XML4Pharma) were used.Results: Through exchange of a complete clinical study between two different study software solutions, a Proof of Concept of the technical feasibility of a system-independent metadata exchange was conducted successfully. The interchange of study metadata between two different systems at different centers was performed with minimal expenditure. A small number of mistakes had to be corrected in order to generate a syntactically correct ODM file and a “vendor extension” had to be inserted. After these modifications, XTrial exhibited the study, including all data fields, correctly. However, the optical appearance of both CRFs (case report forms) was different.Conclusions: ODM can be used as an exchange format for clinical studies between different study software. Thus, new forms of cooperation through exchange of metadata seem possible, for example the joint creation of electronic study protocols or CRFs at different research centers. Although the ODM standard represents a clinical study completely, it contains no information about the representation of data fields in CRFs.
Keywords: Standardization; clinical trial; medical informatics; metadata; CDISC